Association between clinical, radiological, and hematological profile of children with pneumonia - Timilsina, Mukunda; Basnet, Sahisnuta; Mishra, Aparna (Journal of Kathmandu Medical College, 2022)
Background: Patients with pneumonia present with varying symptoms, X-ray features and changes in the blood parameters.Objectives: To find out the association between clinical, radiological, and haematological profile of children with pneumonia.Methods: An analytical cross-sectional study was conducted in 130 children aged two to 60 months admitted to the paediatric ward of Manipal Teaching Hospital, who were chosen by convenience sampling technique from December 2019 to November 2020, and clinical, radiological and haematological parameters compared. The observed data were analysed using SPSS 20.Results: . Of the 130 children studied, 80 (61.5%) were male and 50 (38.5%) were female. History of prior admission for respiratory illness was seen in 75 (57.7%) patients Bronchopneumonia was seen in 72 (55.4%) patients and lobar pneumonia in 37 (28.5%) patients. Cough 122 (93.8%), Noisy breathing 86 (66.15%), Fever 70 (53.84%) and Fast breathing 67 (51.54%) were the most common presenting complaints. Patients with lobar pneumonia were more likely to present with fever than those with Bronchopneumonia (p-value 0.015). Those with history of prior admission were more likely to present with wheeze (p-value 0.035) and crepitations (p-value 0.024) than those admitted for the first time. Also, those presenting with crepitations as lung finding, were found to present with significantly lower total White blood cells (WBC) counts (p-value 0.012).Conclusion: There seems to be a significant association between fever as presenting complaint and lobar pneumonia. Also, those with history of prior admission are more likely to have lung signs (wheeze/crepitations) at presentation.